Congenital pulmonary fibrosarcoma in a newborn with hypoglycemia and respiratory distress: case report - Şahin, Davut; Koç, Nermin; Etker, Şeref; Güven, Şirin; Canpolat, Cengiz (The Turkish Journal of Pediatrics, 2010)
Although primary bronchopulmonary fibrosarcoma is a rare tumor, it may be characterized by the symptoms of acute respiratory distress occurring during the first moments of life in a newborn. It is one of the leading congenital malignant neoplasms of the lung, but is considered a borderline tumor since its biological behavior is much more favorable than that of adult fibrosarcomas. In the absence of metastases, complete resection is curative. Histopathological diagnosis is not simple, as the microscopic characteristics may be confused with benign fibromatosis or malignant mesenchymal neoplasms. In this case report, we present a case of congenital pulmonary spindle cell tumor showing the features of fibrosarcoma, and we discuss the differential diagnosis of spindle cell lesions localized within the thorax.